A method for determining ripeness of an oil palm fruit bunch - Mohamed Sharif, Abdul Rashid; Mohd. Hazir, Mohd. Hafiz; Saripan, M. Iqbal; Amiruddin, Mohd. Din; Ramli, Abdul Rahman (2011)
The present invention relates to a method for determining ripeness of an oil palm fruit bunch (2), characterized by the steps of: emitting one or more lights in a determined wavelength band onto a surface region of the oil palm fruit bunch (2); detecting the fluorescence signals reflected from the oil palm fruit bunch (2); obtaining an absorbance value from the fluorescence signals reflected from the oil palm fruit bunch (2);obtaining an absorbance value from florescence signals detected; applying the absorbance value to a predetermined formula for classification of the oil palm fruit bunch (2) into ripeness category. In a preferred embodiment, the fluorescence lights are blue green light with 447nm wavelength and far red light with 735nm wavelength, both using 373nm wavelength ultraviolet excitation light. In a preferred embodiment, the absorbance value is the ratio of the blue green fluorescence light signal to the far red fluorescence light signal.